Original paperTransvascular pulmonary valve implantation – early results of the first Polish experience - Rużyłło, Witold; Włodarska, Elżbieta K.; Demkow, Marcin; Śpiewak, Mateusz; Sondergaard, Lars; Kowalski, Mirosław; Małek, Łukasz A.; Petryka, Joanna; Siudalska, Hanna; Wolski, Piotr; Miśko, Jolanta; Hoffman, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2009)
Aim: Assessment of early results of the pulmonary artery valve transvascular implantation (PAVTI). Methods: Study group consisted of 4 patients (3 women), aged 27-31 years, with pulmonary homograft dysfunction (stenosis in all patients and concomitant pulmonary regurgitation in two of them). The reasons for homograft implantation were total repair of tetralogy of Fallot (2 patients) and Ross procedure due to congenital aortic valve stenosis (2 patients). Qualification to PAVTI was based on clinical evaluation, echocardiographic studies and assessment of morphological and functional features of right ventricle and homograft with the use of cardiac magnetic resonance (CMR). The procedure was performed in general anesthesia and consisted of two consecutive stages. At first a metal stent was implanted in the pulmonary valve position. Thereafter, it was followed by the deployment of a valved stent. Results were evaluated by echocardiography two days after the procedure. About 1 month after PAVTI patients were examined with echocardiography and CMR. Results: Time of the procedure varied 60-150 min. PAVTI was successfully performed in all patients. Average reduction of pulmonary gradient after the procedure assessed by echocardiography was 56% after 2 days and 65% after one month. No pulmonary regurgitation was observed. In all patients end-systolic and end-diastolic volumes of the right ventricle were reduced with concomitant increase of these parameters for the left ventricle. Conclusions: Pulmonary artery valve transvascular implantation is an effective and safe method of non-surgical treatment for patients with homograft dysfunction.